Accounting Profession: African Perspective Review of steps into the future : African Perspective Review of steps into the future - Kamau, Charles Guandaru; Ilamoya, Sheila Lyona (Multidisciplinary Journal of Technical University of Mombasa, 2023)
The advancement of technology has resulted in significant changes in the way accountants conduct their business. The purpose of this paper was to explore the various perspectives of the effects of technology on the future outlook of the accounting profession. The perspectives explored include the relationship between the accounting profession and the world revolution, the nature of accounting and its relationship with technology, the future of accounting, and changes in accounting education. This paper employed a literature review methodology. This research found that a number of studies indicated that there has to be a shift in the way accounting professionals do their business. Apparently, the transformation has begun to take shape, gradually but surely. This study also observed that this shift in the accounting profession will have an effect on accounting education. The paper concludes that there are certain aspects of the accounting profession that are likely to be transformed by technological advancement; however, the foundations of the accounting profession remain intact.